Minimally Invasive versus Open Distal Pancreatectomy for Ductal Adenocarcinoma (DIPLOMA): A Pan-European Propensity Score Matched Study. Issue 1 (January 2019) - van Hilst, Jony; de Rooij, Thijs; Klompmaker, Sjors; Rawashdeh, Majd; Aleotti, Francesca; Al-Sarireh, Bilal; Alseidi, Adnan; Ateeb, Zeeshan; Balzano, Gianpaolo; Berrevoet, Frederik; Björnsson, Bergthor; Boggi, Ugo; et al.
Abstract : Objective: The aim of this study was to compare oncological outcomes after minimally invasive distal pancreatectomy (MIDP) with open distal pancreatectomy (ODP) in patients with pancreatic ductal adenocarcinoma (PDAC). Background: Cohort studies have suggested superior short-term outcomes of MIDP vs. ODP. Recent international surveys, however, revealed that surgeons have concerns about the oncological outcomes of MIDP for PDAC. Methods: This is a pan-European propensity score matched study including patients who underwent MIDP (laparoscopic or robot-assisted) or ODP for PDAC between January 1, 2007 and July 1, 2015. MIDP patients were matched to ODP patients in a 1:1 ratio. Main outcomes were radical (R0) resection, lymph node retrieval, and survival. Results: In total, 1212 patients were included from 34 centers in 11 countries. Of 356 (29%) MIDP patients, 340 could be matched. After matching, the MIDP conversion rate was 19% (n = 62). Median blood loss [200 mL (60–400) vs 300 mL (150–500), P = 0.001] and hospital stay [8 (6–12) vs 9 (7–14) days, P < 0.001] were lower after MIDP. Clavien-Dindo grade ≥3 complications (18% vs 21%, P = 0.431) and 90-day mortality (2% vs 3%, P > 0.99) were comparable for MIDP and ODP, respectively. R0 resection rate was higher (67% vs 58%, P = 0.019), whereas Gerota's fascia resection (31% vs 60%, P < 0.001) and lymph node retrieval [14 (8–22) vs 22 (14–31), P < 0.001] were lower after MIDP. Median overall survival was 28 [95% confidence interval (CI), 22–34] versus 31 (95% CI, 26–36) months ( P = 0.929). Conclusions: Comparable survival was seen after MIDP and ODP for PDAC, but the opposing differences in R0 resection rate, resection of Gerota's fascia, and lymph node retrieval strengthen the need for a randomized trial to confirm the oncological safety of MIDP. Abstract : Supplemental Digital Content is available in the text